THE INFLUENCE OF MACHINED TOPOGRAPHY ON THE HCF BEHAVIOUR OF THE Al7050 ALLOY. (2018) - Abroug, F.; Pessard, E.; Germain, G.; Morel, F.; Chové, E.
Abstract: The aim of this study is to identify the impact of High Speed Machining defects on the fatigue behaviour of the Al7050 aluminium alloy. A vast experimental campaign under fully reversed plane bending loads containing different surface states has been undertaken to characterize the effect of the surface topography on the fatigue behaviour. The results show that the fatigue strength decreases only when the surface roughness is significantly degraded. It is also pointed out that manual grinding eliminates the effect of the machining defects on the fatigue behaviour. In order to predict the influence of the surface condition on the fatigue behaviour, a numerical approach based on the real surface topology has been developed. It is shown that the numerically identified crack initiation sites are in agreement with the experimental results. A probabilistic approach based on the weakest link concept, associated with the definition of a stress based crack initiation threshold has been integrated in a FE model. This approach leads naturally to a probabilistic Kitagawa type diagram, which in this case explains the relationship between the size defect and the scale effect on the fatigue strength.